Key Determinants of Local Bean Production and Marketing in Mbeya District, Tanzania - Mwidege, Asheri Mandesu (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Common beans are a widely cultivated crop in East and Central Africa. This study aimed to assess the factors affecting local bean production and marketing at the household level. Using a non-experimental research design, the study surveyed 111 farmers from the Isangati division in Mbeya District. Cross-sectional data were collected through expert sampling methods, and regression analysis was employed to examine the influence of socio-economic factors on the production and marketing of local bean varieties. The results indicated that variables such as age, education, occupation, and farm size significantly influenced bean production (p<0.01), as did market accessibility and the acceptability of bean varieties (p<0.01). The study concluded that proximity to markets, socio-economic conditions, and consumer preferences play a crucial role in shaping bean production and marketing outcomes. As a result, interventions should be tailored to meet both user and consumer preferences.